2003
DOI: 10.1046/j.1528-1157.2003.38102.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hippocampal Glucose Oxidation Capacity and Interictal FDG‐PET in Temporal Lobe Epilepsy

Abstract: Summary:Purpose: Interictal [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography (PET) demonstrates temporal hypometabolism in the epileptogenic zone of 60-90% of patients with temporal lobe epilepsy. The pathophysiology of this finding is still unknown. Several studies failed to show a correlation between hippocampal FDG-PET hypometabolism and neuronal cell loss. Because FDG is metabolized by hexokinase bound to the outer mitochondrial membrane, we correlated the glucose-oxidation capacity of hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
5
49
0
2
Order By: Relevance
“…However, this was only statistically significant for unlabeled glucose, not for [1-13 C]glucose, likely because the percentage of enrichment in glucose was only 18%, thus the differences might have been too small to be detectable. This decreased consumption is in agreement with animal and human data showing interictal hypometabolism within the hippocampus, which could extend to extratemporal cortical and subcortical regions (Arnold et al, 1996;Dube et al, 2001;Vielhaber et al, 2003b;Chassoux et al, 2004). Moreover, in these areas neuronal loss does not necessarily correlate with interictal hypometabolism (Ryvlin et al, 1991;O'Brien et al, 1997;Foldvary et al, 1999;Dube et al, 2001).…”
Section: Glucose Metabolismsupporting
confidence: 90%
“…However, this was only statistically significant for unlabeled glucose, not for [1-13 C]glucose, likely because the percentage of enrichment in glucose was only 18%, thus the differences might have been too small to be detectable. This decreased consumption is in agreement with animal and human data showing interictal hypometabolism within the hippocampus, which could extend to extratemporal cortical and subcortical regions (Arnold et al, 1996;Dube et al, 2001;Vielhaber et al, 2003b;Chassoux et al, 2004). Moreover, in these areas neuronal loss does not necessarily correlate with interictal hypometabolism (Ryvlin et al, 1991;O'Brien et al, 1997;Foldvary et al, 1999;Dube et al, 2001).…”
Section: Glucose Metabolismsupporting
confidence: 90%
“…Other investigators used CIV histochemistry, estimated by optical density, to demonstrate neuronal loss and a non-homogenous decrease in CIV activity in piriform cortex of adult rats after pilocarpine- (Otáhal et al 2005). Others have shown that interictal FDG-PET hypometabolism in adult patients with temporal lobe epilepsy was correlated with decreased respiratory chain glucose-oxidation capacity, suggesting the possibility of an intrinsic metabolic abnormality (Vielhaber et al 2003). Although ETC biochemistry was not determined by the investigators, their histological examination suggested CIV deficiency in pyramidal neurons in the CA3 region of hippocampal resections (Vielhaber et al 2003).…”
Section: Importance Of Complex IVmentioning
confidence: 99%
“…A special element of the paralimbic system, the insula-orbital-temporal complex, projects from the temporal pole cortex to insular cortex, i.e., to the long anterior and posterior gyrus of the insula [Augustine, 1996;Eberstaller, 1887;Mesulam and Mufson, 1982a]. The negatively loaded parahippocampal gyrus in the PC3 image, extending bilaterally from the basis of temporal lobe medially and probably including the dentate gyrus, is known to show suppressed metabolism in interictal PET studies of fluorodeoxyglucose [Foldvary et al, 1999;Vielhaber et al, 2003]. The implication of the dentate gyrus in the inhibition of seizures is substantiated by studies of rodents and humans.…”
Section: Temporal Lobe and Insular Cortexmentioning
confidence: 99%